Comparison of Taste and Smell Test Results Before and After COVID-19 in Yakumo Residents Health Checkup ― Comparison between 2019 and 2022 ― (Global Journal of Medical Research, 2022)
Abstract not found
Keywords: simple salty taste test; simple olfactory test; resident medical examination; age group